Defining the characteristics of spherical Janus particles by investigating the behavior of their corresponding particles at the oil/water interface in a Pickering emulsion. Issue 7 (3rd July 2017) - Sharifzadeh, Esmail; Salami-Kalajahi, Mehdi; Salami Hosseini, Mahdi; Razavi Aghjeh, Mir Karim; Najafi, Saeed; Jannati, Roqaye; Hatef, Zahra
ABSTRACT: In this study, a new analytical/experimental method is proposed in order to investigate the adsorption of different-sized spherical silica particles at the oil/water interface in a Pickering emulsion system as a well-known method to produce Janus particles. Accordingly, the characteristic of the produced silica Janus particles was defined based on their penetration depth into dispersed oil droplets. To ensure the accuracy of the method, the penetration depth of silica particles was also measured using field emission scanning electron microscopy images of solidified oil droplets covered with particles. The results revealed that the penetration depth increases with the size of the particles. GRAPHICAL ABSTRACT: